A Messy State of the Union: Taming the Composite State Machines of TLS - Beurdouche, Benjamin; Bhargavan, Karthikeyan; Delignat-Lavaud, Antoine; Fournet, Cédric; Kohlweiss, Markulf; Pironti, Alfredo; Strub, Pierre-Yves; Zinzindohoue, Jean Karim (2015 IEEE Symposium on Security and Privacy, 2015)
Implementations of the Transport Layer Security (TLS) protocol must handle a variety of protocol versions and extensions, authentication modes, and key exchange methods. Confusingly, each combination may prescribe a different message sequence between the client and the server. We address the problem of designing a robust composite state machine that correctly multiplexes between these different protocol modes. We systematically test popular open-source TLS implementations for state machine bugs and discover several critical security vulnerabilities that have lain hidden in these libraries for years, and have now ﬁnally been patched due to our disclosures. Several of these vulnerabilities, including the recently publicized FREAK ﬂaw, enable a network attacker to break into TLS connections between authenticated clients and servers. We argue that state machine bugs stem from incorrect compositions of individually correct state machines. We present the ﬁrst veriﬁed implementation of a composite TLS state machine in C that can be embedded into OpenSSL and accounts for all its supported ciphersuites. Our attacks expose the need for the formal veriﬁcation of core components in cryptographic protocol libraries; our implementation demonstrates that such mechanized proofs are within reach, even for mainstream TLS implementations.
Distinguished Paper